On the Philosophy of Diseases and Medicine – An Opinion - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2023)
The history of medicine tells us that there was a holistic view regarding health and illness among earlier healers. This was the case, for example, in the healing center of Hippocrates on the Greek island of Kos. In contrast, today's conventional medicine has degenerated, it knows a lot about many details, but almost nothing about the wholeness. The symptoms are treated, not the underlying causes. Also not taken into account are: the lifestyle, the habits, the patterns, the motivations, the conflicts, the family ties, the psyche, the soul and the spirit. It is time for medical science to take a holistic approach again if it wants to heal rather than just suppress.